An Ethnolinguistic Content of Dayak and Malay Culture in English Language Teaching: Its Impact on Students’ Reading and Speaking Proficiency - Oxtapianus Tawarik; Wanda Giovani; Efrika Siboro; Yunika Upa (Journal of Educational Learning and Innovation (ELIa), 2026)
Senior high school students in rural and inland areas of Indonesia often exhibit low English proficiency due to limited exposure, reduced instructional time, and teaching materials disconnected from local cultural contexts. In Landak Regency, West Kalimantan, students face difficulties in reading comprehension and high anxiety in speaking English. This pre-experimental study (one-group pretest–posttest) examined the impact of integrating Dayak ethnolinguistic content into English instruction on these skills. Participants were 120 purposively selected students from four public senior high schools. The intervention integrated Dayak folktales, local narratives, culturally loaded vocabulary, and role-playing activities. Data from parallel reading comprehension tests and analytic speaking assessments were analyzed using paired-sample t-tests and effect size calculations. Student performance increased from elementary to intermediate levels, with speaking gains (Mean increase = 18.5, SD = 5.2) slightly exceeding reading gains (Mean increase = 15.2, SD = 4.8). These findings demonstrate that integrating Dayak ethnolinguistic content is an effective and culturally sustainable approach for enhancing English skills in rural educational contexts. This study contributes to the development of culturally responsive English language learning by utilizing local knowledge as a learning resource to boost engagement and strengthen cultural identity.